In silico Analyses of Core Proteins and Putative Effector and Immunity Proteins for T6SS in Enterohemorrhagic E. coli - Vazquez-Lopez, Jaime; Navarro-Garcia, Fernando (Frontiers in Cellular and Infection Microbiology, 2020)
Shiga-toxin-producing Escherichia coli (STEC) has become an important pathogen that can cause diarrhea, hemorrhagic colitis and hemolytic uremic syndrome (HUS) in humans. Recent reports show that the type VI secretion system (T6SS) from EHEC is required to produce infection in a murine model and its expression has been related to a higher prevalence of HUS. In this work, we use bioinformatics analyses to identify the core genes of the T6SS and compared the differences between these components among the two published genomes for EHEC O157:H7 strain EDL933. Prototype strain EDL933 was further compared with other O157:H7 genomes. Unlike other typical T6SS effectors found in E. coli, we identified that there are several rhs family genes in EHEC, which could serve as T6SS effectors. In-silico and PCR analyses of the differences between rhs genes in the two existing genomes, allowed us to determine that the most recently published genome is more reliable to study the rhs genes. Analyzing the putative tridimensional structure of Rhs proteins, as well as the motifs found in their C-terminal end, allowed us to predict their possible functions. A phylogenetic analysis showed that the orphan rhs genes are more closely related between them than the rhs genes belonging to vgrG islands and that they are divided into three clades. Analyses of the downstream region of the rhs genes for identifying hypothetical immunity proteins showed that every gene has an associated small ORF (129-609 nucleotides). These genes could serve as immunity proteins as they had several interaction motifs as well as structural homology with other known immunity proteins. Our findings highlight the relevance of the T6SS in EHEC as well as the possible function of the Rhs effectors of EHEC O157:H7 during pathogenesis and bacterial competition, and the identification of novel effectors for the T6SS using a structural approach.